2006
DOI: 10.1016/j.jinsphys.2005.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Role of membrane transport of water and glycerol in the freeze tolerance of the rice stem borer, Chilo suppressalis Walker (Lepidoptera: Pyralidae)

Abstract: Overwintering larvae of the rice stem borer, Chilo suppressalis accumulate glycerol and are freezing tolerant to about -25°C. However, non-diapausing larvae cannot accumulate glycerol and are killed by freezing. We compared the extent of tissue damage, the effects of glycerol concentration, and the transport of glycerol and water in fat body tissues from these larvae at selected freezing temperatures. Tissues from overwintering larvae, but not non-diapausing larvae, survive when frozen at -20°C with 0.25M glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 21 publications
1
65
0
Order By: Relevance
“…RNA insertion and protein overexpression of aquaporins successfully increases the survival of mouse oocytes during cryopreservation (Edashige, 2003) and the viability of baker's yeast in bread dough after freezing (Tanghe et al, 2002). In addition, a recent report by Izumi et al (Izumi et al, 2006) provides evidence that aquaporins promote freeze tolerance in a rice stem boring insect. By blocking the functionality of the protein with mercuric chloride, a known inhibitor of some aquaporins (Preston et al, 1993), they reported a reduction in cell survival during freezing.…”
Section: Introductionmentioning
confidence: 99%
“…RNA insertion and protein overexpression of aquaporins successfully increases the survival of mouse oocytes during cryopreservation (Edashige, 2003) and the viability of baker's yeast in bread dough after freezing (Tanghe et al, 2002). In addition, a recent report by Izumi et al (Izumi et al, 2006) provides evidence that aquaporins promote freeze tolerance in a rice stem boring insect. By blocking the functionality of the protein with mercuric chloride, a known inhibitor of some aquaporins (Preston et al, 1993), they reported a reduction in cell survival during freezing.…”
Section: Introductionmentioning
confidence: 99%
“…The permeability of AQP/GLPs to these molecules implicates these proteins in protecting against freeze-induced damage in a range of organisms, including yeast (Tanghe et al, 2002), insects (Izumi et al, 2006;Philip et al, 2008) and amphibians (Zimmerman et al, 2007). The ability of EsAQP1 channels to redistribute water across the membrane faster than by simple diffusion through membrane, as shown by our in vitro assay (Fig.4), would facilitate cellular dehydration that is caused by the formation of concentrated extracellular fluid during freezing.…”
Section: Functional Characterization Of Esaqp1mentioning
confidence: 76%
“…AQPs, which rapidly redistribute water and certain small solutes across the membrane, are associated with the physiological response to stresses that require the management of cellular water, such as anhydrobiosis (Kikawada et al, 2008), feeding on osmotically challenging foods (Le Caherec et al, 1996;Shakesby et al, 2009) and survival of freezing (Izumi et al, 2006;Philip et al, 2008;Philip and Lee, 2010). To better understand the role of these proteins in osmotic stress, we identified, functionally characterized the water permeability and determined the tissue distribution of an AQP during seasonal cold acclimation in E. solidaginis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations